The Decarbonisation Challenge of Southeast Europe: A Case Study of Romania - Radu Dudău; Mihnea Cătuţi (Intereconomics, 2019)
Not only is Romania facing some crucial energy system problems, but the proposed solutions have often been improvised and incoherent. This also raises doubts about the effectiveness of strategic planning aimed at implementing the energy transition to net-zero emissions by 2050.
Keywords: 330